Habitat Associations of Damselfish in Reefs of Varying Quality in The Wakatobi Marine National Park - Ahmadia, Gabby N; Turner, Joseph A; Smith, David J. (Journal of Indonesian Coral Reefs, 2012)
Damselfishes are an abundant, specious group of fishes that are important functional components in coral reef systems. Many of these species have strong habitat associations thus are sensitive to changes in the coral reef habitat quality. The purpose of this study was to investigate the distributional patterns of damselfish in different coral reef zones in healthy and degraded reefs. Benthic and fish transects were carried out in different reef zones from the patch reef to reef slope. Life history changes and microhabitat associations were recorded for all damselfish species. Higher numbers of both adults and juveniles were found on the healthy reef, Hoga. Damselfish communities were also more distinct between zones on the healthy Hoga reef compared to the degraded Sampela reef likely attributed to the more homogenous benthic composition among zones in Sampela. Significantly lower numbers of juveniles were found on the reef slope, with no significant difference between the other three zones, indicating ontogenetic migration of adults into deeper zones. When abundance was analysed at species level more distinct patterns were observed. Damselfish clearly have preferences for particular microhabitat types, and this influences their overall distribution on coral reefs. Changes in fish communities between healthy and degraded reefs were observed as well, though it is less clear how this influences the dynamics of coral reefs. This study further reiterates the strength and nature of habitat associations of damselfish and provides insight into potential changes in distribution patterns when there is a decrease in overall habitat quality.